2017
DOI: 10.1039/c7ra04421f
|View full text |Cite
|
Sign up to set email alerts
|

Shedding light on the effective fluorophore structure of high fluorescence quantum yield carbon nanodots

Abstract: The unique luminescence properties of carbon nanodots (CDs) originate from pyridone-like fluorophores bound to carbon core.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(117 citation statements)
references
References 41 publications
5
104
1
2
Order By: Relevance
“…The characteristic fluorescence of CDs mainly originates from these two domains . It is reported that photoexcited electrons assigned to the π → π* transition were likely relax into either the sp 2 energy levels or the surface states, bringing about short‐ or long‐wavelength PL, respectively . In this work, we believe that nitrogen‐derived structures in carbon cores and n → π* transitions of surface functionalized CO and CN groups of porphyrins are responsible for the dual long‐wavelength emissions of CDs (Figure f).…”
Section: Resultsmentioning
confidence: 61%
“…The characteristic fluorescence of CDs mainly originates from these two domains . It is reported that photoexcited electrons assigned to the π → π* transition were likely relax into either the sp 2 energy levels or the surface states, bringing about short‐ or long‐wavelength PL, respectively . In this work, we believe that nitrogen‐derived structures in carbon cores and n → π* transitions of surface functionalized CO and CN groups of porphyrins are responsible for the dual long‐wavelength emissions of CDs (Figure f).…”
Section: Resultsmentioning
confidence: 61%
“…For instance, at low synthesis temperature molecular uorophores dominate the PL, while at high temperature they are more extensively carbonized and PL comes under the control of aromatic domains. 52,53 All the herein described CDs displayed intrinsic uorescence properties, except CD1 and CD7 that were produced at 100 C. It is assumed that at such low temperature, neither PAH domains nor molecular uorophores could form in signicant amount. The UV absorption of the other CDs at 250 nm did not typically generate uorescence as can be observed on the PL excitation spectrum for each nanoparticle (Fig.…”
Section: Characterization Of Cdsmentioning
confidence: 97%
“…50 One of the rst approaches envisioned energy transfer between distinct states associated with the core, incorporating PAH domains, and the surface of the CD as the likely source of the observed optical properties. Another model was proposed that involves the formation of molecular uorophores during the synthesis of the CDs (such as citrazinic acid and 2-pyridonebased molecules [50][51][52] ) that signicantly contribute to their emission. It thus appears that PL may result from combined contributions of PAH domains and molecular uorophores, depending on the preparation procedure.…”
Section: Characterization Of Cdsmentioning
confidence: 99%
“…Высокий выход PL квантовых точек был получен для столь же широкой области спектра за счет изменения их размера [61]. Уанг и соавторы [62], исследуя синтезированные ими CQD из лимонной кислоты и различных диаминов, пришли к заключению, что высоким выходом флуоресценции обладают структуры производных пирамидона.…”
Section: углеродные квантовые точкиunclassified
“…Уанг и соавторы [73], исследуя сверхбыстрые процессы в графеновых квантовых точках, пришли к заключению, что осуществляющийся за 1.5 ps после поглощения света процесс соответствует переносу энергии от ядра точки к периферической пирамидоновой молекулярной структуре. В работе [74] были изучены с помощью пикосекундных измерений PL и фемтосекундного лазерного фотолиза графеновые квантовые точки.…”
Section: процессы релаксации в Cqdunclassified